Steel, Administered Prices and Inflation - Adelman, M. A. (Quarterly Journal of Economics, 1961)
I. Introduction, 16. — II. “Administered prices,” 18. — III. The problem in steel, 20. — IV. Interdependence of costs and prices, 21. — V. Price determination in steel, 23. — VI. The crisis of 1959, 29. — VII. Public policy, 35. — Epilogue, 38.